PENCIPTAAN KEUNGGULAN BERSAING PERUSAHAAN MELALUI PENINGKATAN PERILAKU PELAYANAN - Hendriyanto, Asepta (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
The purpose of this research is to investigate and analyze the factors thataffect the competitive advantage through service behavior. The method usedis the method of survey data obtained directly through questionnaires.Sampling using sensus sampling methods and methods of analysis used inthis research was the path analysis. Based on the research results revealedthat organizational communication, and service culture have effect on servicebehavior. And variable service behavior have effect of the firm competitiveadvantage.